Trade Union Growth, Structure and Policy — A Comparative Study of the Cotton Unions in England - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1963)
The article reviews the book, "Trade Union Growth, Structure and Policy — A Comparative Study of the Cotton Unions in England," by H.A. Turner.